Machine Learning Approaches to TCR Repertoire Analysis - Katayama, Yotaro; Yokota, Ryo; Akiyama, Taishin; Kobayashi, Tetsuya J. (Frontiers in Immunology, 2022)
Sparked by the development of genome sequencing technology, the quantity and quality of data handled in immunological research have been changing dramatically. Various data and database platforms are now driving the rapid progress of machine learning for immunological data analysis. Of various topics in immunology, T cell receptor repertoire analysis is one of the most important targets of machine learning for assessing the state and abnormalities of immune systems. In this paper, we review recent repertoire analysis methods based on machine learning and deep learning and discuss their prospects.